Lower Bounds for the Principal Eigenvalue of the p-Laplacian on the Unit Ball. (3rd October 2018) - Aghajani, A.; Tehrani, A. Mosleh
Abstract: In this paper, by the sub-super solution method we provide explicit lower bounds for the principal eigenvalue of the p -Laplacian on the unit ball. We compare our results with those of earlier studies and also demonstrate that they are in good agreement with numerical results.